UNDERSTANDING PHILOSOPHY IN CONCEPTS KNOWLEDGE - Novialdi Novi (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2024)
The philosophy of science clarifies the existence of science with other sciences which require knowledge as a medium of thinking and a means of scientific communication. These are language, mathematical logic, statistics and other data analysis techniques. The specifications and independence of science are faced with the increasing number of problems that science cannot answer. therefore, philosophy emerged as the answer. Philosophy provides explanations or answers to substantial and radical problems, while science continues to develop itself within its limits, while still being radically criticized, processes or interactions are basically the field of philosophy of science, therefore, philosophy of science can be placed as an effort to bridge the gap. between philosophy and science, so that science does not hate philosophy and philosophy does not hate science as a shallow understanding of nature. Reality is "what is natural" or existence, while its appearance is "artificially real" also how the relationship between the two with the subject/human epistemology is considered identical to The theory of knowledge at this time the theory of knowledge cannot be ignored. The epistemology of science education is related to knowing how science education obtains profit processing, what are the procedures for obtaining correct knowledge. Axiology related with What excess education science What ethical connection ethical with science And its implementation education science in life daily .